Multidimensional Poverty in Ethiopia : Changes in Overlapping Deprivations - Ambel, Alemayehu; Mehta, Parendi; Yigezu, Biratu (World Bank, Washington, DC, 2015)
This paper presents trends in monetary and nonmonetary dimensions of wellbeing in Ethiopia using data from the Household Consumption and Expenditure and Welfare Monitoring surveys implemented in 2000, 2005, and 2011. The paper provides evidence on changes in overlapping deprivations using a non-index approach to multidimensional poverty. It assesses the performance of various dimensions in education, health, and living standards, taking one indicator at a time. It then examines the overlap between different dimensions of poverty and examines how this has changed over time in Ethiopia and across rural and urban areas. It highlights that although Ethiopia’s multidimensional poverty index is very high, there have been improvements in overlapping deprivations and, as a result, the number of individuals deprived in multiple dimensions has fallen.